The impact of galaxy selection on the splashback boundaries of galaxy clusters. Issue 1 (28th March 2022) - O'Neil, Stephanie; Borrow, Josh; Vogelsberger, Mark; Diemer, Benedikt
ABSTRACT: We explore how the splashback radius ( R sp ) of galaxy clusters, measured using the number density of the subhalo population, changes based on various selection criteria using the IllustrisTNG cosmological galaxy formation simulation. We identify R sp by extracting the steepest radial gradient in a stacked set of clusters in 0.5 dex wide mass bins, with our clusters having halo masses 10 13 ≤ M 200, mean /M⊙ ≤ 10 15 . We apply cuts in subhalo mass, galaxy stellar mass, i -band absolute magnitude, and specific star formation rate. We find that, generally, galaxies of increasing mass and luminosity trace smaller measured splashback radii relative to the intrinsic dark matter radius. We also show that quenched galaxies may be used to reliably reconstruct the dark matter splashback radius. This trend is likely due to changes in the galaxy population. Additionally, we are able to reconcile different observational predictions that R sp based upon galaxy number counts and dark matter may either align or show significant offset (e.g. those using optically or SZ-selected clusters) through the selection functions that these studies employ. Finally, we demonstrate that changes in R sp measured through number counts are not due to a simple change in galaxy abundance inside and outside of the cluster.